POST-TRANSPLANT LYMPHOPROLIFERATIVE DISORDERS: ROLE OF VIRAL INFECTION, GENETIC LESIONS AND ANTIGEN STIMULATION IN THE PATHOGENESIS OF THE DISEASE - Daniela Capello; Gianluca Gaidano (Mediterranean Journal of Hematology and Infectious Diseases)
Post-transplant lymphoproliferative disorders (PTLD) are a life-threatening complication of solid organ transplantation or, more rarely, hematopoietic stem cell transplantation. The majority of PTLD is of B-cell origin and associated with Epstein–Barr virus (EBV) infection. PTLD generally display involvement of extranodal sites, aggressive histology and aggressive clinical behavior. The molecular pathogenesis of PTLD involves infection by oncogenic viruses, namely Epstein-Barr virus, as well as genetic or epigenetic alterations of several cellular genes. At variance with lymphoma arising in immunocompetent hosts, whose genome is relatively stable, a fraction of PTLD are characterized by microsatellite instability as a consequence of defects in the DNA mismatch repair mechanism. Apart from microsatellite instability, molecular alterations of cellular genes recognized in PTLD include alterations of cMYC, BCL6, TP53, DNA hypermethylation, and aberrant somatic hypermutation of protooncogenes. The occurrence of IGV mutations in the overwhelming majority of PTLD documents that malignant transformation targets germinal centre (GC) B-cells and their descendants both in EBV–positive and EBV–negative cases. Analysis of phenotypic markers of B-cell histogenesis, namely BCL6, MUM1 and CD138, allows further distinction of PTLD histogenetic categories. PTLD expressing the BCL6+/MUM1+/-/CD138- profile reflect B-cells actively experiencing the GC reaction, and comprise diffuse large B-cell lymphoma (DLBCL) centroblastic and Burkitt lymphoma. PTLD expressing the BCL6-/MUM1+/CD138- phenotype putatively derive from B-cells that have concluded the GC reaction, and comprise the majority of polymorphic PTLD and a fraction of DLBCL immunoblastic. A third group of PTLD is reminiscent of post-GC and preterminally differentiated B-cells that show the BCL6-/MUM1+/CD138+ phenotype, and are morphologically represented by either polymorphic PTLD or DLBCL immunoblastic.